Hubungan Antara Efek Samping Pengobatan Dengan Kepatuhan Pengobatan Pasien Tb Paru Di Puskesmas Bangetayu Semarang - Amelia Putri Khoirunnisa; Ahmad Ikhlasul Amal; Erna Melastuti (An-Najat, 2025)
Pulmonary tuberculosis is a chronic infectious disease that has become a global health problem, with Indonesia ranked 3rd in the world after India, China and South Africa. In 2022 the discovery of pulmonary TB was 98.1% with a cure rate of only 46.8%. Patients with pulmonary TB in Semarang City reached 4,653 cases. Objective To analyze the relationship between OAT side effects and treatment compliance of pulmonary TB patients. This study is an analytic descriptive study using a cross sectional approach, the research subjects consisted of 56 respondents with pulmonary TB. The sampling technique used was total sampling, the data were analyzed by univariate test using frequency distribution, bivariate test using fisher test, data collection using questionnaire with side effect questionnaire and treatment compliance questionnaire. The results obtained received a p-value of 0.002 (Pα) that there is an association between side effects of treatment on treatment adherence in patients with pulmonary tuberculosis. Conclusion: we can draw a value of 0.002 (Pα). This can lead to the conclusion that there is an association between side effects of medication and treatment adherence in patients with pulmonary tuberculosis.